2003
DOI: 10.1128/mcb.23.21.7767-7779.2003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Properties of Nucleosomes during Thermal and ATP-Driven Mobilization

Abstract: The fundamental subunit of chromatin, the nucleosome, is not a static entity but can move along DNA via either thermal or enzyme-driven movements. Here we have monitored the movements of nucleosomes following deposition at well-defined locations on mouse mammary tumor virus promoter DNA. We found that the sites to which nucleosomes are deposited during chromatin assembly differ from those favored during thermal equilibration. Taking advantage of this, we were able to track the movement of nucleosomes over 156 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
105
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 69 publications
11
105
1
Order By: Relevance
“…This implies that in vivo nucleosome occupancy is determined by the DNA sequence that wraps the full octamer rather than the ðH3∕H4Þ 2 tetramer. Such behavior is much like the shifted positions that are preferred after thermal or enzymatic remodeling of in vitro reconstituted chromatin fragments (5,41) and emphasizes the central role of chromatin remodelers in in Local Deviations from the Predicted Nucleosome Occupancy. Above we maintained a strict statistical mechanics description of nucleosome positioning with a minimal number of free parameters and assumed that the thermodynamic properties of all nucleosomes were identical.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…This implies that in vivo nucleosome occupancy is determined by the DNA sequence that wraps the full octamer rather than the ðH3∕H4Þ 2 tetramer. Such behavior is much like the shifted positions that are preferred after thermal or enzymatic remodeling of in vitro reconstituted chromatin fragments (5,41) and emphasizes the central role of chromatin remodelers in in Local Deviations from the Predicted Nucleosome Occupancy. Above we maintained a strict statistical mechanics description of nucleosome positioning with a minimal number of free parameters and assumed that the thermodynamic properties of all nucleosomes were identical.…”
Section: Resultsmentioning
confidence: 78%
“…2B) (30). The fact that in vitro reconstitution does not yield nucleosomes at their thermodynamically most favorable positions has been observed by Flaus and Owen-Hughes (41). They showed that sites to which nucleosomes are deposited during chromatin assembly on a mouse mammary tumor virus substrate differ from those favored during thermal equilibration or enzymatic remodeling Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Furthermore, during remodeling by either SWI/SNF or the SWI/SNF-family remodeler RSC, a small gap placed in various locations on the nucleosome will move from its initial position to a defined final position about two turns from the dyad 38,41 . Finally, mononucleosomes remodeled by SWI/SNF or RSC move the free DNA end to a final position about two turns from the dyad 28,38,41,45 . Together, these observations strongly suggest that the translocase domain pumps DNA from this internal position on the nucleosome and that the arrival of a DNA gap or end at this position stops translocation 38,41,43,44 .…”
Section: Remodelers Can Translocate Dna From a Fixed Internal Sitementioning
confidence: 99%
“…These thermodynamic properties underlie the very slow translational movement of nucleosomes in vitro by thermal diffusion 28 and their extremely slow rates of spontaneous disassembly and ejection. These properties also establish the energetic obstacles that remodelers must overcome and are important for interpreting the measurements obtained in single-molecule experiments (Fig.…”
mentioning
confidence: 99%
“…However, nucleosome positions established during salt-dialysis assembly can be altered by treatment at elevated temperatures (e.g. (24,25,45,(47)(48)(49)(50)), suggesting that mammalian body temperature might promote some level of nucleosome redistribution in vivo. Thermal repositioning is most rapid at high temperatures (up to 65°C) and in the absence of divalent cations or linker histones (45,48,51,52)).…”
Section: Hswi/snf-favored Positions Differ From Thermally Favored Posmentioning
confidence: 99%